A new species of Astyanax Baird & Girard (Characiformes: Characidae) from the upper rio Araguaia, Central Brazil - Oliveira, Carlos Alexandre Miranda; Pavanelli, Carla Simone; Bertaco, Vinícius Araújo (Zootaxa, 2017)
We describe a new species of Astyanax from the upper rio Araguaia basin, Mato Grosso State, Brazil. The new species presents a combination of characters that indicates its allocation within the A. scabripinnis species complex. The new species differs from congeners belonging to the A. scabripinnis species complex by a combination of the following characters: lateral dark stripe beginning immediately behind the upper margin of the opercle; a single vertical humeral dark blotch; a scattered pattern of dark chromatophores below lateral line, at the abdominal region; 15 to 20 branched anal-fin rays; lateral line with 33 to 36 perforated scales; dentary teeth decreasing abruptly in size from the fourth or fifth tooth onwards; and 13 or 14 circumpeduncular scales.